Pengembangan Konten Multimedia Berbasis Case Method pada Sistem Pengelolaan Pembelajaran (SIPEJAR) Mata Kuliah Konseling Humanistik - Apriani, Rizka; Ramli, M; Indreswari, Henny; Hidayatullah, Hengki Tri; Hermawan, Salsabila Yuli Adys (citeus, 2025)
Guidance and counseling students as prospective counselors are required to have professional competence, especially in the process of counseling services. Humanistic counseling is one of the courses that must be mastered by students. This study aims to develop multi-media SIPEJAR content based on the case method for humanistic counseling courses. This research adapts the Research and Development model with stages of analysis, design, development, implementation, and evaluation. The instrument uses an accessibility rating scale to measure the acceptability of the prototype. The data uses percentage descriptive techniques and qualitative data to be obtained from criticism and suggestions. There are six types of media that are constructed into multimedia such as 1) motion graphics; 2) infographics; 3) presentation slides; 4) twelve handouts/handbooks; 5) audio; and 6) explainer videos. The results of the test assessment of media experts, materials, and prospective users showed a high score. It can be concluded that the case-method-based multimedia content for humanistic counseling courses developed meets accessibility including accuracy, usefulness, ease, and attractiveness and meets the criteria of being very accurate, very useful, very easy, and very interesting so that humanistic counseling learning can be implemented.